The end of theory financial crises, the failure of economics, and the sweep of human interaction - Bookstaber, Richard M. 1950 (Princeton, NJ Princeton University Press, 2017)
"An in-depth look at how to account for the human complexities at the heart of today's financial system Our economy may have recovered from the Great Recession--but not our economics. In The End of Theory, Richard Bookstaber, one of the world's leading risk managers, discusses why the human condition and the radical uncertainty of our world renders the standard economic model--and the theory behind it--useless for dealing with financial crises. What model should replace it? None. At least not any version we've been using for the past two hundred years. Instead, Bookstaber argues for a new approach called agent-based economics, one that takes as a starting point the fact that we are humans, not the optimizing automatons that standard economics assumes we are. Bookstaber's groundbreaking paradigm promises to do a far better job at preventing crises and managing those that break out. As he explains, our varied memories and imaginations color our economic behavior in unexpected hues. Agent-based modeling embraces these nuances by avoiding the mechanistic, unrealistic structure of our current economic approach. Bookstaber tackles issues such as radical uncertainty, when circumstances take place beyond our anticipation, and emergence, when innocent, everyday interactions combine to create sudden chaos. Starting with the realization that future crises cannot be predicted by the past, he proposes an approach that recognizes the human narrative while addressing market realities. Sweeping aside the historic failure of twentieth-century economics, The End of Theory offers a novel and innovative perspective, along with a more realistic and human framework, to help prevent today's financial system from blowing up again. "--Provided by publisher.
Machine generated contents note: -- I: Introduction 1 1 Crises and Sunspots 3 2 Being Human 14 II: The Four Horsemen 23 3 Social Interactions and Computational Irreducibility 25 4 The Individual and the Human Wave: Emergent Phenomena 34 5 Context and Ergodicity 40 6 Human Experience and Radical Uncertainty 50 7 Heuristics: How to Act Like a Human 65 III: Paradigm Past And Future 79 8 Economics in Crisis 81 9 Agent-Based Models 94 10 Agents in the Complexity Spectrum 108 IV: Agent-Based Models For Financial Crises 125 11 The Structure of the Financial System: Agents and the Environment 127 12 Liquidity and Crashes 144 13 The 2008 Crisis with an Agent-Based View 157 V: The End Of Theory 169 14 Is It a Number or a Story? Model as Narrative 171 15 Conclusion 185 Acknowledgments 191 Notes 193 References 211 Index 221.
Includes bibliographical references and index.
Keywords: Financial crises -- Forecasting; Economics; Human behavior; Business and economics -- theory; Business and economics -- Finance